Doebner-type pyrazolopyridine carboxylic acids in an Ugi four-component reaction - Murlykina, M. M.; Kolomiets, O. V.; Kornet, M. M.; Sakhno, Y. I.; Desenko, S. M.; Dyakonenko, V. V.; Shishkina, S. V.; Brazhko, O. A.; Musatov, V. I.; Tsygankov, A. V.; Van der Eycken, E. V.; Chebanov, V. A. (BioMed Central, United Kingdom, 2019)
Substituted 1H-pyrazolo[3,4-b]pyridine-4- and 1H-pyrazolo[3,4-b]pyridine-6-carboxamides have been synthetized through a Doebner–Ugi multicomponent reaction sequence in a convergent and versatile manner using diversity generation strategies: combination of two multicomponent reactions and conditions-based divergence strategy. The target products contain as pharmacophores pyrazolopyridine and peptidomimetic moieties with four points of diversity introduced from readily available starting materials including scaffold diversity. A small focused compound library of 23 Ugi products was created and screened for antibacterial activity.
Keywords: antibacterial activity; Doebner reaction; pyrazolo[3,4-b]pyridine carboxylic acids; Ugi reaction